Small bowel enema in non-responsive coeliac disease. Issue 8 (August 1990) - Mike, N; Udeshi, U; Asquith, P; Ferrando, J
Abstract : A small bowel enema was performed in patients with non-responsive coeliac disease, in coeliac patients on a normal diet (untreated) and those who had shown a good response to a gluten free diet, and in control subjects to determine whether there were any specific radiological features of the non-responsive state. A significant reduction in the average number of jejunal folds and an increase in the number of ileal folds (reversal of the jejunoileal fold pattern) was found in eight of nine non-responsive coeliac patients, one of seven untreated coeliac patients, and in none of the good responders or control subjects. This pattern identifies coeliac patients with a poor response to a gluten free diet who are likely to suffer major complications.